Chapter 7 The Hell That Black People Live: Trump's Reports to Journalists on Urban Conditions - Guniss, Carolyn (Taylor & Francis, 2018)
This book examines the disruptive nature of Trump news - both the news his administration makes and the coverage of it - related to dominant paradigms and ideologies of U.S. journalism. By relying on conceptualizations of media memory and "othering" through news coverage that enhances socio-conservative positions on issues such as immigration, the book positions this moment in a time of contestation. Contributors ranging from scholars, professionals, and media critics operate in unison to analyze today's interconnected challenges to traditional practices within media spheres posed by Trump news. The outcomes should resonate with citizens who rely on journalism for civic engagement and who are active in social change